APLIKASI IMPORTANCE- PERFORMANCE ANALYSIS DALAM MENILAI KUALITAS PELAYANAN PEMBUATAN KARTU Ak.1 PADA DINAS TENAGA KERJA DAN TRANSMIGRASI KABUPATEN CILACAP - Zul Irmaini; Sugiarti . (LPPM Universitas Pekalongan, 2010)
The purposes of this research are to analyze the quality of making Ak.1 card service at The Office of Labor and Transmigration of the Cilacap Regency and to determine The largest service variable which influence the quality of making Ak.1 card service. Based upon these purposes , two hypotheses are developed:First The quality of making Ak.1 card service (tangible, reliability, responsiveness, assurance,empathy) has confirmed with the expectancy of the job seekers , second Empathy is the most influential variable upon making Ak-1 card service.The method of this research is a Survey and instrument of analysis employed is Importance Performance analysis. Results of analysis show findings as follows : The performance of service is lower than The importance or expectancy of service, Thus the first hyphotesis stating that the quality of service of making Ak.1 card done by the office of Labor and Transmigration of the Cilacap Regency has confirmed with the expectancy of job seekers is not supported. According to the job seekers,the Empathy variable is one that has the smallest value, so the second hyphotesis is that states the empathy variable influences the service of making Ak-1 card , is supported.Keywords : Importance – Performance analysis .